Shaking‐table tests of flat‐bottom circular silos containing grain‐like material. (15th August 2015) - Silvestri, Stefano; Ivorra, Salvador; Chiacchio, Laura Di; Trombetti, Tomaso; Foti, Dora; Gasparini, Giada; Pieraccini, Luca; Dietz, Matt; Taylor, Colin
Summary: According to Eurocode 8, the seismic design of flat‐bottom circular silos containing grain‐like material is based on a rough estimate of the inertial force imposed on the structure by the ensiled content during an earthquake: 80% of the mass of the content multiplied by the peak ground acceleration. A recent analytical consideration of the horizontal shear force mobilised within the ensiled material during an earthquake proposed by some of the authors has resulted in a radically reduced estimate of this load suggesting that, in practice, the effective mass of the content is significantly less than that specified. This paper describes a series of laboratory tests that featured shaking table and a silo model, which were conducted in order to obtain some experimental data to verify the proposed theoretical formulations and to compare with the established code provisions. Several tests have been performed with different heights of ensiled material – about 0.5 mm diameter Ballotini glass – and different magnitudes of grain–wall friction. The results indicate that in all cases, the effective mass is indeed lower than the Eurocode specification, suggesting that the specification is overly conservative, and that the wall–grain friction coefficient strongly affects the overturning moment at the silo base. At peak ground accelerations up to around 0.35  g, the proposed analytical formulation provides an improved estimate of the inertial force imposed on such structures by their contents. Copyright © 2015 John Wiley & Sons, Ltd.